A dual threshold listen-before-talk for unlicensed LTE systems - Kim, Jae Hoon; Choi, Sungchul (Eurasip Journal on Wireless Communications and Networking, 2019)
The insufficient wireless frequency bands are likely to arise with the increase in mobile traffic demand. Many mobile operators suffer from a high annual increase in the cost of licensed wireless bands. Unlicensed bands present a potential opportunity for mobile operators. A single 5-GHz band with a large bandwidth provides faster transmission for each user. However, interference caused by existing wireless transmissions, such as Wi-Fi in unlicensed bands, is a serious issue in the effective utilization of unlicensed bands by mobile operators. The Listen-Before-Talk (LBT) was proposed as a promising method to ensure the coexistence of Wi-Fi and commercial mobile services such as LTE. We focus on effective control of the contention window (CW) size to maximize the operability of LBT. Control of the CW size depends on the repetition of extended clear channel assessment (ECCA). We introduce a dual threshold system that counts the repetition of ECCA. The newly developed NS-3-based unlicensed band network simulator shows the effectiveness of the proposed control mechanism. The results indicated that the advantage of the proposed method improves 4.3–7.6% than traditional LBT method. We develop a composite metric of throughput and fairness to evaluate the performance of LTE-LAA access.
Keywords: 5 GHz; Coexistence; ECCA; Simulation; Unlicensed; 5 GHz; Coexistence; ECCA; LBT; LTE; ns-3; Simulation; Unlicensed; Wi-Fi